1993
DOI: 10.1002/prs.680120403
|View full text |Cite
|
Sign up to set email alerts
|

Case study of a hydrogen peroxide related deflagration in a wastewater treatment tank

Abstract: On August 3, 1991, at about 12:20 pm, a deflagration occurred inside a wastewater treatment tank at the Allied‐Signal Delaware Plant. The tank was being used to hold treated wastewater prior to discharge to the plant process sewer system. One minor injury occurred as a result of the deflagration. The tank sustained damage to its manway, conservation assembly, and inlet and discharge piping. The building in which the tank was located had to have relief panels and roofing replaced and required repairs to the wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…30 Previously it has been used in effluent treatment, soil bioremediation, industrial gas treatment and recovery of metals from Li-ion batteries. 30,31 Therefore, it is important to study the effect of H 2 O 2 addition on metal leaching from WEEE.…”
Section: Introductionmentioning
confidence: 99%
“…30 Previously it has been used in effluent treatment, soil bioremediation, industrial gas treatment and recovery of metals from Li-ion batteries. 30,31 Therefore, it is important to study the effect of H 2 O 2 addition on metal leaching from WEEE.…”
Section: Introductionmentioning
confidence: 99%
“…The water slug mechanism might have relevance for other “closed vessel” explosions involving gassy reactions and elevated oxygen concentrations. A case in point is Allied‐Signal's wastewater tank explosion discussed a quarter century ago at the 1993 Loss Prevention Symposium . The investigation included the scenario “corona discharge generated by cascading liquids” but this was considered unlikely.…”
Section: Water Slug Sparking Mechanismmentioning
confidence: 99%
“…There is a previously reported incident where decomposing hydrogen peroxide in a tank released oxygen, and the solvent vapour in the tank ignited. This was investigated by Pratt who concluded that the mechanism was that the bursting bubbles formed highly charged droplets and the corona discharges from the resultant electrostatic field ignited the vapour in the atmosphere in the tank.…”
Section: The Hazardmentioning
confidence: 99%